2020
DOI: 10.7717/peerj.8921
|View full text |Cite
|
Sign up to set email alerts
|

Androgen up-regulation of Twist1 gene expression is mediated by ETV1

Abstract: Twist1, a basic helix-loop-helix transcription factor that regulates a number of genes involved in epithelial-to-mesenchymal transition (EMT), is upregulated in prostate cancer. Androgen regulation of Twist1 has been reported in a previous study. However, the mechanism of androgen regulation of the Twist1 gene is not understood because the Twist1 promoter lacks androgen receptor (AR)-responsive elements. Previous studies have shown that the Twist1 promoter has putative binding sites for PEA3 subfamily of ETS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A previous study revealed that AR could upregulate TWIST1 via ETV1 in prostate cancer [ 45 ]. Similarly in RCC cells, AR can also increase TWIST1 expression through an indirect mechanism through lncRNA-TANAR to impact RCC VM development.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that AR could upregulate TWIST1 via ETV1 in prostate cancer [ 45 ]. Similarly in RCC cells, AR can also increase TWIST1 expression through an indirect mechanism through lncRNA-TANAR to impact RCC VM development.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, AKT1 is capable of enhancing the phosphorylation of twist family bHLH transcription factor 1 (Twist1), which is required for β-TrCP-mediated Twist1 ubiquitination and degradation [ 15 ]. Twist1, an essential helix-loop-helix transcription factor, is known to regulate numerous genes related to epithelial-to-mesenchymal transition [ 16 ]. In addition, previous research illustrated that the methylation of DNA in the promoter region of Twist1 was a crucial mechanism in osteoblastic differentiation of MSCs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…ETV1 binds to many target genes and plays a role in tumor progression and metastasis by regulating expression of them. It has previously been shown to confer the aggressive biologic behavior of tumors via inhibition of checkpoint kinase 1 (CHK1), upregulation of EMT-associated genes such as TWIST1, SNAIL, HAS2, pro-metastatic genes such as MMP1/7, SPARC , methyltransferase METTL3 [20,[49][50][51][52][53]. Herein, we uncovered that PTK2 and c-MET were transcriptional targets of ETV1.…”
Section: Discussionmentioning
confidence: 94%